MADEIRA AND JANE EYRE'S COLONIAL INHERITANCE. Issue 2 (5th May 2017) - Valint, Alexandra
Abstract : The denouement of Charlotte Brontë's Jane Eyre contains multiple happy rewards for its heroine: a fortune, strangers turned friends turned cousins, the self-elimination of Bertha, and a Rochester still alive, still in England, and now free to marry. The hefty twenty-thousand-pound legacy (of which Jane only keeps one-fourth) bequeathed to her by her late uncle John Eyre allows Jane to return to the maimed Rochester and gleefully proclaim, "I am an independent woman now" (Brontë 501; ch. 37). Citing such financial independence, Sandra Gilbert and Susan Gubar briefly mention Jane's inheritance as the event that allows Jane to "follow her own will" and marry Rochester on terms of equality (367). Similarly, Nancy Armstrong writes that "[m]ore so perhaps than her virtue or passion, it is an endowment from Jane's wealthy uncle that makes her happiness possible" (47). Other critics, such as Elaine Freedgood and Susan Meyer, focus on the origin of the fortune – Madeira – and suggest that such a colonially associated locale implicates Jane in the finances of colonialism and even of slavery. Unlike those critics, however, I will claim that Jane's complicated relationship to the inheritance distances her from the problematic taint of the money's colonial associations and marks her non-conformity with and resistance to the economic practices of the British Empire.